Joleen Callahan and Mae Dailey - Unknown:::Creator::::::::::::
Photograph shows Joleen Callahan in center of photograph with Mae Dailey on the left, at a table waiting with sign-in sheets for the y-Walk. There are Y-Walk stickers on their clothes and a red and white y-Walk balloon bouquet behind them. The table has signs instructing walkers to sign in under their team captain's name and a span of alphabetical letters to direct people where to sign in.